The Foundations of Corporate Strategies; Comment on "'Part of the Solution': Food Corporation Strategies for Regulatory Capture and Legitimacy" - William H. Wiist (Kerman University of Medical Sciences, 2022)
The "Part of the Solution" article describes how the food industry has evolved its strategies to respond to critics and government regulation by co-option and appeasement to create a less hostile environment. Rather than focusing research on single industries it would be more efficient and productive to focus on corporate political activities (CPAs) that directly influence democratic institutions and processes having authority over laws, policy, rules and regulations that govern industry. The most influential and direct CPA are election campaign donations, lobbying, and the reverse revolving door (RRD). In the United States those CPA flow from rights of corporations that underlie all industry strategies. The US history of how corporations obtained their rights is described, and research about the affirmative effects of those three CPA is summarized. Health research is needed about those CPA and their effects on health law, policy and regulation in the United States and other nations.